Lapatinib ameliorates skin fibrosis by inhibiting TGF-β1/Smad and non-Smad signaling pathway - Yongping Wang; Tiantian Zhang; Hao Song; Cheng Yang (Scientific Reports)
Abstract Skin fibrosis, characterized by excessive accumulation of extracellular matrix (ECM) in the dermis, can lead to hypertrophic scars and impaired mobility. The ErbB family of receptor tyrosine kinases, including ErbB1 and ErbB2, plays a crucial role in organ fibrosis, but their specific impact on skin fibrosis is less understood. This study investigated the role of ErbB1 and ErbB2 in skin fibrosis and the therapeutic potential of lapatinib, a dual ErbB1 and ErbB2 tyrosine kinase inhibitor. Using qPCR, cell culture assays, Western blotting, and in vivo models, we found significant upregulation of ErbB1 and ErbB2 in keloid tissues and fibroblasts. Lapatinib treatment resulted in a dose-dependent decrease in ErbB1 and ErbB2 expression, which suppressed the expression of fibroblast activation markers. Our findings suggest that lapatinib may be a promising therapeutic agent for skin fibrosis by targeting ErbB1/ErbB2 and modulating the TGF-β1/Smad2/3/Erk/Akt signalling pathways. These results warrant further clinical investigation into lapatinib for treating skin fibrosis and related conditions.